Assessing the corporate social responsibility interventions in the Ghanaian oil and gas industry: Perspectives from local actors. (December 2022) - Mohammed, Asaah Sumaila; Ackah, Ishmael; Tuokuu, Francis Xavier; Abane, Sussana
Highlights: CSR means different people to different companies. Using a social license theory, we assess CSR initiatives within the extractive industry in Ghana. Less than half of beneficiaries are involved in decision-making regarding CSR initiatives. Beneficiaries also have no knowledge of the cost of projects. We conclude the study with effective social strategies that may be applicable in other jurisdictions. Abstract: Corporate Social Responsibility (CSR) has been identified as an effective strategy for oil and gas companies to obtain a social license from their host communities. Within Ghana's oil and gas sector, different companies have developed and implemented many social interventions as part of their CSR initiatives meant to achieve win-win outcomes and to gain legitimacy from host communities. Based on primary data and guided by the social license to operate (SLO) model, the study examines community perceptions and experiences of the CSR initiatives of oil and gas companies operating in Ghana. We find that the impact of projects on communities vary from place to place. This variation is due to the level of involvement of communities in project conception and implementation, capacity building of programs, the nature of post implementation management, and the cost and preparedness for the maintenance of projects. Specifically, 48% of the respondents indicated that they are involved in the CSR decisions of oil and gas companies. Despite this level of involvement, 98% of the respondents had no knowledge of the cost of the interventions provided by the oil and gas companies. Clearly, while there is an average local participation in CSR decisions, there appears to be information asymmetry in the implementation of these activities. We conclude with some practical implications for the development and implementation of effective CSR interventions within the oil and gas sector in Ghana that may be applicable in other countries.